PENGARUH KUALITAS PELAYANAN, SANKSI PERPAJAKAN, BIAYA KEPATUHAN PAJAK DAN PENERAPAN E-FILING PADA KEPATUHAN WAJIB PAJAK - Nayong Azhaki Damayanti; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACT               This research was conducted to see the effect of Service Quality Variables, Tax Sanctions, Tax Imposition, and E-Filing Implementation that supports taxation at the Ngawi Pratama Tax Office, the sample in this study were 100 taxpayer respondents. The method used in this research was multiple linear regression analysis with the help of SPSS For windows application. Simultaneous testing results show the variable service quality, tax penalties, tax costs, and the application of e-filing affect the tax. The test results show partial service quality, tax penalties, and the application of e-positive filing affect tax approval. While the variable costs of applying negative taxes on taxpayer approval.Keywords: Service Quality, Tax Sanctions, Tax Compliance Costs, Application of E-Filing, Tax Compliance.